Liquid computing : a structured approach to identifying incremental risks and controls resulting from autonomous synchronisation - Visser, Alwyn Jacobus Nicolaas (Stellenbosch : Stellenbosch University, 2017)
Thesis (MCom)--Stellenbosch University, 2017.